New Feminist Perspectives on the History of the Twentieth Century. Issue 1 (1st March 2019) - Feinberg, Melissa
Abstract : Maria Bucur, Gendering Modernism: A Historical Reappraisal of the Canon, London: Bloomsbury Academic, 2017, xi + 149 pp., 24.95 (paperback), ISBN: 978-1-3500-2625-4. Maria Bucur, The Century of Women: How Women Have Transformed the World Since 1900, Lanham, MD: Rowman and Littlefield, 2018, x + 232 pp., 35.00 (paperback), ISBN: 978-1-4422-5739-9.